THE INFLUENCE MECHANISMS OF ILLEGITIMATE TASKS ON EMPLOYEES’ SILENCE BEHAVIORS AGAINST THE BACKDROP OF ARTIFICIAL INTELLIGENCE AND FUZZY ALGORITHMS - Zhou, Baohuan; Hu, Xiaoli; Tang, Qinglong; Xie, Yundong; Zhu, Yaozong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Employee silence can degrade the working environment and decrease employees’ motivation and commitment to an organization. As a result, it not only affects employees but also reduces the productivity of the organization. However, few studies have investigated the influencing mechanisms of employee silence empirically. This paper studies how illegitimate tasks affect employee silence based on artificial intelligence and fuzzy algorithms. We surveyed 325 employees in several medium-sized enterprises in Jiangsu and Anhui, China. According to the findings, emotional exhaustion partially mediates the relationship between illegitimate tasks and employees’ silence behaviors, and leadership humor can moderate the positive effect of illegitimate tasks on emotional exhaustion. Therefore, situating the mechanisms underlying employees’ silence behaviors in the context of artificial intelligence and fuzzy algorithm research helps researchers understand the relationship between illegitimate tasks and employees’ silence behaviors, thus improving related research on silence behaviors.